PANCASILA SEBAGAI PARADIGMA ILMU: LANDASAN FILOSOFIS, ETIS, DAN EPISTEMOLOGIS - Sianipar, Nathania Arabella (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Pancasila, as Indonesia’s foundational ideology and philosophy, holds a strategic role in developing science rooted in both local and universal values. This article examines Pancasila as a scientific paradigm, focusing on three fundamental dimensions: philosophical, ethical, and epistemological. A qualitative approach through literature review and critical analysis explores the relevance of Pancasila's values in addressing the multidimensional challenges of modern science. The findings reveal that Pancasila serves as a holistic and integrative conceptual framework, merging spiritual, rational, and empirical aspects in scientific practices. A Pancasila-based paradigm offers an inclusive and sustainable approach to advancing science that prioritizes not only technological progress but also social and environmental well-being.